Replacement of Marine Fish Oil with de novo Omega‐3 Oils from Transgenic Camelina sativa in Feeds for Gilthead Sea Bream (Sparus aurata L.). Issue 10 (2nd September 2016) - Betancor, Mónica B.; Sprague, M.; Montero, D.; Usher, S.; Sayanova, O.; Campbell, P. J.; Napier, J. A.; Caballero, M. J.; Izquierdo, M.; Tocher, D. R.
Abstract: Omega‐3 (n‐3) long‐chain polyunsaturated fatty acids (LC‐PUFA) are essential components of the diet of all vertebrates. The major dietary source of n‐3 LC‐PUFA for humans has been fish and seafood but, paradoxically, farmed fish are also reliant on marine fisheries for fish meal and fish oil (FO), traditionally major ingredients of aquafeeds. Currently, the only sustainable alternatives to FO are vegetable oils, which are rich in C18 PUFA, but devoid of the eicosapentaenoic (EPA) and docosahexaenoic acids (DHA) abundant in FO. Two new n‐3 LC‐PUFA sources obtained from genetically modified (GM) Camelina sativa containing either EPA alone (ECO) or EPA and DHA (DCO) were compared to FO and wild‐type camelina oil (WCO) in juvenile sea bream. Neither ECO nor DCO had any detrimental effects on fish performance, although final weight of ECO‐fed fish (117 g) was slightly lower than that of FO‐ and DCO‐fed fish (130 and 127 g, respectively). Inclusion of the GM‐derived oils enhanced the n‐3 LC‐PUFA content in fish tissues compared to WCO, although limited biosynthesis was observed indicating accumulation of dietary fatty acids. The expression of genes involved in several lipid metabolic processes, as well as fish health and immune response, in both liver and anterior intestine were altered in fish fed the GM‐derived oils. This showed a similar pattern to that observed in WCO‐fed fish reflecting the hybrid fatty acid profile of the new oils. Overall the data indicated that the GM‐derived oils could be suitable alternatives to dietary FO in sea bream.